STRATEGI KOMUNIKASI HUMAS APVI (ASOSIASI PERSONAL VAPORIZER INDONESIA) DI MEDIA SOSIAL INSTAGRAM DALAM MENINGKATKAN CITRA ROKOK ELEKTRIK SEBAGAI ALTERNATIF ROKOK TEMBAKAU - Ariq Abdul Aziz, (2024)
The phenomenon that occurred involved individuals selling vape liquids by mixing them with drugs. This reality led to a decline in the image of vape cigarettes. The initiative was taken by the united community of vape enthusiasts in Indonesia, forming the Indonesian Personal Vaporizer Association (APVI). The initial goal of establishing APVI was to legalize vaping. As time passed and vaping became legal in Indonesia, the focus shifted to combating the circulation of illegal liquids containing drugs.This research aims to understand APVI's public relations strategies in building the image of electronic cigarettes as a tobacco alternative through the Instagram platform. Additionally, the study aims to identify APVI's efforts in socializing and campaigning related issues through social media. The theoretical framework used in this research is the formative research phase and public relations by Harwood Childs. The research method employed is a qualitative case study, collecting data through observation, interviews, and relevant literature studies.The research findings indicate that APVI's public relations strategy in building the image of electronic cigarettes involves various programs such as campaigns, social activities, and the effective use of Instagram as a tool. In the context of strengthening the image of electronic cigarettes, APVI collaborates with communities, universities, and government institutions such as the Police, BNN (National Narcotics Agency), and Customs to support its programs.